Quantitative Lung Ultrasound: Technical Aspects and Clinical Applications. (5th April 2021) - Mongodi, Silvia; De Luca, Daniele; Colombo, Andrea; Stella, Andrea; Santangelo, Erminio; Corradi, Francesco; Gargani, Luna; Rovida, Serena; Volpicelli, Giovanni; Bouhemad, Bélaid; Mojoli, Francesco
Abstract : Lung ultrasound is increasingly used in emergency departments, medical wards, and critical care units—adult, pediatric, and neonatal. In vitro and in vivo studies show that the number and type of artifacts visualized change with lung density. This has led to the idea of a quantitative lung ultrasound approach, opening up new prospects for use not only as a diagnostic but also as a monitoring tool. Consequently, the multiple scoring systems proposed in the last few years have different technical approaches and specific clinical indications, adaptable for more or less time-dependent patients. However, multiple scoring systems may generate confusion among physicians aiming at introducing lung ultrasound in their clinical practice. This review describes the various lung ultrasound scoring systems and aims to clarify their use in different settings, focusing on technical aspects, validation with reference techniques, and clinical applications. Abstract : Lung ultrasound permits reliable assessment and monitoring of lung aeration. Multiple scoring systems have been developed in recent years with specific technical aspects, and this article describes how to apply this technique in the appropriate clinical context.